Disease duration of rheumatoid arthritis is a predictor of vascular stiffness: a cross-sectional study in patients without known cardiovascular comorbidities: A STROBE-compliant article - Vázquez-Del Mercado, Mónica; Gomez-Bañuelos, Eduardo; Chavarria-Avila, Efrain; Cardona-Muñoz, Ernesto; Ramos-Becerra, Carlos; Alanis-Sanchez, Adrián; Cardona-Muller, David; Grover-Paez, Fernando; Perez-Vazquez, Felipe de J.; Navarro-Hernandez, Rosa-Elena; Valadez-Soto, Jorge M.; Saldaña-Millan, Adan A.; et al. (Medicine (Baltimore), 2017)
The aim of this study was to analyze the impact of disease duration on carotid to femoral pulse wave velocity (cfPWV) in rheumatoid arthritis (RA) patients without either known traditional cardiovascular risk factors or previous comorbidities.Patients with RA diagnosis attending the rheumatology outpatient clinic of Hospital Civil Juan I. Menchaca, Guadalajara, Mexico, were analyzed. A total of 106 RA patients without known traditional cardiovascular risk factors were selected. All subjects were evaluated for RA disease duration, RA disease activity score on 28 joints (DAS28), serum lipids, rheumatoid factor and anti-cyclic citrullinated peptide (anti-CCP) antibodies. Arterial stiffness was measured as cfPWV by noninvasive tonometry. A multivariate regression model was used to analyze the contribution of RA disease duration and age on cfPWV. cfPWV was positively correlated with age (r = 0.450, P < .001), RA disease duration (r = 0.340, P < .001), total cholesterol (r = 0.312, P = .002), and low density lipoprotein (LDL-c) cholesterol (r = 0.268, P = .012). Patients with a RA disease duration ≥10 years exhibited significantly increased cfPWV compared with patients with disease duration <2 years (8.4 ± 1.8 vs 7.0 ± 0.8) and ≥2 to <10 years (8.4 ± 1.8 vs 7.8 ± 1.3), respectively. Age, RA disease duration, and triglycerides were predictors of cfPWV in multivariate analyses. According to the β-coefficients, each year of disease duration (β = 0.072) had a greater impact on cfPWV than age (β = 0.054).Each year of life with RA contributes to a higher rate of vascular aging or stiffening than a year of life without RA. The cumulative damage provided by RA was most pronounced in patients with disease duration ≥10 years.